2015
DOI: 10.7314/apjcp.2015.16.6.2501
|View full text |Cite
|
Sign up to set email alerts
|

Level of Knowledge and Behavior of Family Health Personnel Workers in Izmir about Early Diagnosis for Breast and Cervix Cancer

Abstract: Purpose: The present study was carried out to measure knowledge level and behavior of family health personnel (FHP) in Izmir on early diagnosis of breast and cervical cancers. Materials and Methods: The study population of this cross-sectional study was not selected. A questionnaire was applied to all FHP to measure knowledge level and behavior about cancer. The participation rate was 88%. Breast examination, mammography analysis, Papanicolaou smear applications were determined as dependent variables, and know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Consistent with the present study, screening mammography was found to be low in the previous research [ 27 29 ]. It was lower than expected especially considering the fact that participants were HW [ 13 , 30 ]. There have been inadequate studies about knowledge, attitudes, and screening mammography among HW in literature.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with the present study, screening mammography was found to be low in the previous research [ 27 29 ]. It was lower than expected especially considering the fact that participants were HW [ 13 , 30 ]. There have been inadequate studies about knowledge, attitudes, and screening mammography among HW in literature.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, less than half of pharmacists practice BSE, and less than a third performed the screening regularly monthly. This is much lower than the rate for BSE in other studies among female health care professionals in Cameroon [ 13 ], King Saudi Arabia (KSA) [ 26 ], Nigeria [ 23 ], Turkey [ 14 ], and Morocco [ 11 ]. However, our findings were comparable with a study conducted among female healthcare workers in a public health facility in Ethiopia showing low rates of BSE (32.6%) [ 25 ].…”
Section: Discussionmentioning
confidence: 73%
“…Female healthcare professionals have a significant influence on the perspective of female patients regarding screening practices, and they represent a source of positive motivation for women to enhance their awareness and uptake of screening methods for the early detection of the disease [ 11 , 12 ]. Therefore, the level of knowledge, attitude, and practice of breast cancer early detection methods by healthcare professionals are key determinants of their influence on adopting screening methods by women in their communities [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%